'Complete 5p' trisomy: 1 case and 19 translocation carriers in 6 generations. Issue 4 (August 1977) - Brimblecombe, F S; Lewis, F J; Vowles, M
Abstract : A description is given of a female infant with multiple malformations and mental retardation who died at 31 months. Cytogenetic studies indicate trisomy of the complete short arm of chromosome 5, resulting from the unbalanced segregation of a balanced translocation in the mother whose karyotype was interpreted as 46, XX, t(5; 15)(p11; p12). The karyotype of the proband was designated 46, XX, der(5)t(5; 15)(p11; p12)mat. Family studies indicate that the translocation has been present in the family for at least 6 generations.